Legal Protection of Licensees of FIFA World Cup 2014 Brazil Broadcasting Rights Reviewed in the Study of Law Number 28 of 2014 concerning Copyright and Treaty Law - Iqta Adzkia (Green Publisher Indonesia, 2025)
Copyright is an essential component of Hak Kekayaan Intelektual (HKI) that provides exclusive protection to creators and rights holders, including in the context of broadcasting rights for international sports events. In the 2014 FIFA World Cup Brazil, PT Inter Sport Marketing (ISM) obtained an official license from FIFA for the Indonesian territory, including the authority to grant sub-licenses to television stations and public viewing service providers. However, in practice, numerous infringements occurred, such as hotels, restaurants, and cafés organizing public viewing events without official authorization, resulting in economic losses for the license holder. This study aims to analyze the forms of legal protection available to the licensee of World Cup broadcasting rights under Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta and contract law principles. The research employs a normative juridical method with a descriptive-analytical approach based on secondary legal materials. The findings reveal that legal protection is provided in two forms: preventive, through licensing requirements and royalty payments, and repressive, through litigation in commercial and criminal courts. This study underscores the importance of consistent law enforcement to ensure legal certainty, prevent economic losses, and strengthen perlindungan hak cipta in Indonesia.